2014
DOI: 10.1002/2013wr014882
|View full text |Cite
|
Sign up to set email alerts
|

A diameter‐sensitive flow entropy method for reliability consideration in water distribution system design

Abstract: Flow entropy is a measure of uniformity of pipe flows in water distribution systems. By maximizing flow entropy one can identify reliable layouts or connectivity in networks. In order to overcome the disadvantage of the common definition of flow entropy that does not consider the impact of pipe diameter on reliability, an extended definition of flow entropy, termed as diameter-sensitive flow entropy, is proposed. This new methodology is then assessed by using other reliability methods, including Monte Carlo Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 63 publications
0
29
1
Order By: Relevance
“…The results to date seem to indicate that flow entropy (Tanyimboh and Templeman 1993a) yields the most consistent results (Gheisi and Naser 2015;Liu et al 2016). Recent reviews and comparisons include Liu et al (2014Liu et al ( , 2016, , Gheisi and Naser (2015), Atkinson et al (2014) and Greco et al (2012). In particular, Gheisi and Naser (2015) emphasized the importance of failure tolerance while highlighted the need for more consistency in future comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…The results to date seem to indicate that flow entropy (Tanyimboh and Templeman 1993a) yields the most consistent results (Gheisi and Naser 2015;Liu et al 2016). Recent reviews and comparisons include Liu et al (2014Liu et al ( , 2016, , Gheisi and Naser (2015), Atkinson et al (2014) and Greco et al (2012). In particular, Gheisi and Naser (2015) emphasized the importance of failure tolerance while highlighted the need for more consistency in future comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Atkinson et al (2014) observed that an increase in entropy promotes an increase in capacity that is more globally distributed throughout the distribution network. Recently, Liu et al (2014) proposed an extension to the flow entropy function called diameter-sensitive flow entropy. Singh and Oh (2015) incorporated the Awumah et al (1991) entropy formulation in a variant known as Tsallis entropy (Tsallis 1988).…”
mentioning
confidence: 99%
“…Comparisons of surrogate reliability measures include Prasad and Park (2004), Raad et al (2010), Baños et al (2011)), Tanyimboh et al (2011), Wu et al (2011), Greco et al (2012, Atkinson et al (2014), Liu et al (2014) and Gheisi and Naser (2015). While some of the studies simulated operating conditions with insufficient pressure realistically with pressuredependent modelling (Liu et al 2014;Gheisi and Naser 2015), others did not (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations